The Study of Maya Ritual Drawings - Andrea, Andrea (International Journal of Art, Design, and Metaverse, 2023)
The study of ritual drawings in the historical Maya civilization offers profound insights into their religious practices, cosmology, and cultural beliefs. The ancient Maya, known for their remarkable achievements in art and astronomy, left behind a wealth of artwork that played a central role in their rituals and ceremonies. This paper delves into the significance of ritual drawings, their symbolism, and iconography, as well as their connection to the Maya’s religious worldview. A prominent aspect of Maya rituals involved bloodletting, which is vividly portrayed in the ritual drawings. These self-sacrificial acts were performed to offer the gods the life force represented by blood, ensuring harmony in the cosmic order. The Maya’s intricate calendar system was another crucial element in their rituals, with drawings marking significant dates and celestial alignments relevant to their religious events. The study of Maya ritual drawings uses qualitative and quantitative method. A systematic literature review (SLR) is a research method used to identify, evaluate, and synthesize existing scholarly literature on a specific topic. The process is systematic and follows a well-defined set of steps to minimize bias and ensure rigor. The findings suggest that drawings have been utilized as a means of documentation and artistic expression in diverse civilizations, offering a window into their historical and cultural evolution. The prevalence of themes related to civilization, ritual, and religion in the visual representations underscores the enduring impact of these aspects on human societies throughout history.